Non-Isothermal Crystallization Kinetics of Montmorillonite/Polyamide 610 Nanocomposites - Yang Fu; Cuimeng Huo; Shuangyan Liu; Keqing Li; Yuezhong Meng (Nanomaterials, 2023)
Non-isothermal crystallization kinetics of montmorillonite (MMT)/polyamide 610 (PA610) composites were readily prepared by in situ melt polymerization followed by a full investigation in terms of their microstructure, performance, and crystallization kinetics. The kinetic models of Jeziorny, Ozawa, and Mo were used in turn to fit the experimental data, in all of which Mo’s analytical method was found to be the best model for the kinetic data. Differential scanning calorimetry (DSC) and transmission electron microscopy (TEM) studies were used to investigate the isothermal crystallization behavior and MMT dispersion levels in the MMT/PA610 composites. The experiment results revealed that low MMT content can promote the PA610 crystallization, whilst high MMT content result in MMT agglomeration, and reduce the PA610 crystallization rate.